Effects of Elevated Ambient Temperature on Reproductive Outcomes and Offspring Growth Depend on Exposure Time - Huda Yahia Hamid; Md Zuki Abu Bakar Zakaria; Goh Yong Meng; Abd. Wahid Haron; Noordin Mohamed Mustapha (The Scientific World Journal)
Reproductive performance has been shown to be greatly affected by changes in environmental factors, such as temperature. However, it is also crucial to identify the particular stage of pregnancy that is most adversely affected by elevated ambient temperature. The aims of this study were to determine the effect on reproductive outcomes of exposure to elevated ambient temperature during different stages of pregnancy and to determine the effect of prenatal heat stress on offspring growth. Sixty pregnant rats were used in this study. The rats were divided equally into four groups as group 1 (control), group 2 (exposed to elevated temperature following implantation), group 3 (exposed to elevated temperature during pre- and periimplantation), and group 4 (exposed to elevated temperature during pre- and periimplantation and following implantation). Groups 3 and 4 had prolonged gestation periods, reduced litter sizes, and male-biased sex ratios. Moreover, the growth patterns of group 3 and 4 pups were adversely affected by prenatal exposure to elevated temperature. The differences between group 1 and group 3 and between group 1 and group 4 were highly significant. However, no significant differences were observed between groups 1 and 2 in the gestation length, sex ratios, and growth patterns. Thus, it can be concluded that exposure to elevated ambient temperature during pre- and periimplantation has stronger adverse effects on reproductive outcomes and offspring growth than postimplantation exposure.